РЕЖИССЕРСКИЕ ИГРЫ СОЦИАЛЬНОЙ КОММУНИКАЦИИ В СВЕТЕ МАКЕДОНСКОЙ ДРАМЫ (Philological Studies, 2019)
The consideration here is focused on the issue of the self-thematization of the director's theater into the self-referent model of play: «drama into drama» («play into play», «theater in theater»). In Kole Chasule’s and Jordan Plevnesh’s plays the auto-referent drama model put the light on the problem of the relationship between the reality and fiction into the inscenations of the totalitarism – as director’s plays.